Effect of drip irrigation and NPK fertigation on growth, yield, quality and economics of tomatoes (Lycopersicum esculentum) under protected environment - SINGH, JASPREET; SANDAL, SANJEEV K; YOUSUF, ABRAR; BHAT, MOHAMMAD AMIN (Journal of Soil and Water Conservation, 2025)
The present study was conducted during 2018-19 to evaluate the effect of drip irrigation and fertigation levels on growth, fruit yield, quality and economics of tomatoes under protected environment. The experiment consisted of two irrigation schedules, i.e., I1 (Irrigation applied from week one to two based on 100% of pan evaporation (Epan), week three to eight based on 40% of Epan, week nine to fourteen based on 60% of Epan, week fifteen to twenty based on 80% of Epan, week twenty one to twenty four based on 100% of Epan) and I2 (Irrigation applied based on 100% of Epan during the entire crop period) combined with five-nutrient schedules: F1 (100% recommended dose of fertilizers (RDF) through the conventional method), F2 (100% N through fertigation + PK through the conventional method), F3 (100% NK through fertigation + P through the conventional method), F4 (100% NPK through fertigation) and F5 (50% NPK through the conventional method + 150% NPK through fertigation). The results indicated that the marketable yield (7.33 kg/m2), plant height (185.67 cm), titrable acidity (0.52%) and net returns (Rs. 173.12) were significantly higher under I2 treatment but the WUE was significantly higher under I1 treatment. Among the nutrient schedules, plant growth parameters, titrable acidity (0.56%), marketable yield (7.62 kg/m2), water use efficiency and net returns (Rs. 177.80) were higher under F5 treatment. However, the Benefit:Cost (B:C) ratio (3.75) was significantly higher under F4 treatment. The study concluded that irrigation level I2 (irrigation applied based on 100% of Epan during whole of the crop period) with fertigation treatment F4 (100% NPK through fertigation) was most suitable strategy for obtaining the maximum productivity of tomato under protected environment.